Power electronics contribution to renewable energy conversion addressing emission reduction: Applications, issues, and recommendations - Hannan M.A.; Lipu M.S.H.; Ker P.J.; Begum R.A.; Agelidis V.G.; Blaabjerg F. (Elsevier Ltd, 2023)
Carbon; Computational complexity; Controllers; Conversion efficiency; Cost effectiveness; Emission control; Energy conservation; Energy conversion; Energy policy; Energy security; Energy utilization; Fossil fuels; Global warming; Greenhouse gases; Power control; Power converters; Power electronics; Renewable energy resources; Carbon emissions; Electronic controllers; Electronic technologies; Global warming problems; Power electronic converters; Renewable energies; Renewable energy source; Technological innovation; Energy efficiency; alternative energy; carbon emission; electrical power; electronic equipment; emission control; energy efficiency; energy resource; fossil fuel; global warming; innovation